FUN LEARNING FOR ISLAMIC LEARNERS: THE INFLUENCE OF FUN-BASED ENGLISH LEARNING ON SANTRI RESPONSES AT TPQ AT-TAQWA SUKADANA VILLAGE - Medisa Firdausi Nuzula; Audina Qurratul Aini; Rizki Fania; Multazam Ismail; Usuluddin (STMIK Indonesia Banda Aceh, 2026)
This study aims to examine the influence of the Fun Learning for Islamic Learners method on santri responses toward English learning at TPQ At-Taqwa, Sukadana Village. The study was conducted within the framework of a community service program of Universitas Hamzanwadi. A quantitative pre-experimental design with a One Group Pre-Test Post-Test approach was employed, involving 25 santri aged 7 to 13 years selected through purposive sampling from a total population of 45 registered santri. Data were collected using a five-item Likert-scale questionnaire measuring santri responses across affective, cognitive, and behavioral dimensions, which was confirmed to be valid and reliable. The Wilcoxon Signed-Rank Test was applied as the primary analytical method following normality testing. The results indicate a statistically significant difference in santri response scores before and after the implementation of the Fun Learning for Islamic Learners method. The study concludes that fun-based, value-integrated English instruction is effective in improving the engagement and responsiveness of young learners in non-formal Islamic educational settings.